Conflict, caste and resolution: a quantitative analysis for Indian villages. Issue 2 (9th October 2019) - Borooah, Vani Kant; Tagat, Anirudh; Mishra, Vinod
Abstract : Purpose: The purpose of this paper is to provide a quantitative assessment of caste-based conflict in India. The data for this paper are from the Rural Economic and Demographic Survey (REDS) of 2006 encompassing 8, 659 households in 242 villages in 18 Indian states. Design/methodology/approach: Using these data, the authors examine two broad issues: the sources of conflict in rural India and the degree to which these sources contribute to caste-basted, as opposed to non-caste-based conflict; the sources of conflict resolution in rural India: are some conflict-resolving agencies more effective at dealing with caste-based conflicts and others more effective with non-caste-based conflicts? Findings: There was a rise in caste-based conflict over the (approximate) period 1996-2006. There are several reasons for the rise in caste-based conflict but, in the main, is the rise in assertiveness of persons belonging to India's lower castes. In terms of conflict resolution, panchayats and prominent individuals were important in resolving village conflicts: 69 per cent of caste-based, and 65 per cent of non-caste based, conflicts were resolved by one or the other of these two agents. Originality/value: This is the first attempt, using econometric methodology, to study caste conflict at a village level in India.